The Legitimacy of Bougainville Secession from Papua New Guinea - Muhammad Sandy Ilmi (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2021)
What started as a movement to demand a distributive justice in mining revenue in Bougainville, Papua New Guinea, the conflict turned into the struggle for secession. From 1970’s the demand for secession have been rife and despite early agreement for more autonomy and more mining revenue for the autonomous region, the demand never faded. Under Francis Ona’s Bougainville Revolutionary Army, the movement take a new heights. Bougainville Revolutionary Army took coercive measure to push the government to acknowledge their demands by taking over the mine at Panguna. Papua New Guinean government response was also combative and further exacerbate the issue. Papua New Guinean Defense Force involvement adding the issue of human rights into the discourse. This paper will seek to analyze the normative question surrounding the legitimacy of the right to secession in Bougainville Island. The protracted conflict has halted any form of development in the once the most prosperous province of Papua New Guinea and should Bougainville Island become independent, several challenges will be waiting for Bougainvilleans.